Pembelajaran Distribusi Gamma dalam Masalah Biomedis: Tinjauan pada Pengaruh Dosis Beracun pada Tikus: Gamma Distribution Learning in Biomedical Problems: A Review on the Effect of Toxic Doses in Rats - Ramlan, Andi Mariani; Irmasari (Journal of Research in Science and Mathematics Education, 2024)
Purpose: The objective of this study is to examine the use of the Gamma function in the Gamma distribution and its application in analyzing the effect of toxic doses on rats. Methodology: The methodology employed in this study utilizes a non-standard Gamma distribution, with a continuous random variable X that has parameters α and β. The research methods employed in this study include a literature review and a case study. Findings: The results of the calculations indicated that the mean time to death for the rats was 50 weeks, with a standard deviation of 22.36 weeks. Significance: It was also found that the probability of rats surviving for more than 60 days was less than 60%. Based on these findings, the study offers recommendations for the teaching of mathematics, particularly in the context of understanding probability distributions and their applications in biological and toxicological contexts. This study underscores the significance of grasping the Gamma distribution in anticipating and interpreting data in the life sciences, as well as the capacity of mathematical concepts to be operationalized in genuine settings.